2016
DOI: 10.1016/j.apacoust.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Approach for combining physical properties and sensibility for pleasant beverage can-opening sound

Abstract: The sound quality of consumer products has recently become an important feature, receiving much attention in the fields of engineering and manufacturing. The sound could add value to the product in the way that it meets the interests and preferences of consumers in a wide range of fields. The present study deals with the sound emitted from beverage cans when lifting the tab of the can end to open it before drinking. With a view toward finding the characteristics of sound that have a sense of ease and certainty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Future similar work could do the opposite by focusing on the higher frequency/pressure components of the sound stimuli. For instance, previous research found semantic associations between higher-pitched can opening sounds and specific comfort scores [ 18 ]. It may also be interesting to mix those experiential beer sounds with other sound cues that may be part of more realistic virtual retail experiences, such as background noise and/or music.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future similar work could do the opposite by focusing on the higher frequency/pressure components of the sound stimuli. For instance, previous research found semantic associations between higher-pitched can opening sounds and specific comfort scores [ 18 ]. It may also be interesting to mix those experiential beer sounds with other sound cues that may be part of more realistic virtual retail experiences, such as background noise and/or music.…”
Section: Discussionmentioning
confidence: 99%
“…This recent study also showed that the more a sound was associated with a premium beer, the more alive, good, pleasant, and happy the participants evaluated it. As a complement, and concerning hedonic sensations associated with high audible frequency ranges (i.e., pitch), another study also reported that high-pitched product opening sounds were more associated with somewhat positive concepts, such as brisk, comfortable, and secure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, that said, the 'million dollar question' here is whether those assessments of shitsukan, or material quality, that are made under unisensory conditions have any predictive value as far as what people will perceive, or report, under conditions where multiple senses may be used in product evaluation (Ballesteros et al, 2005). Indeed, given that visual dominance is such a ubiquitous feature of our object identification (Posner et al, 1976;Spence, 2011a), the contribution of nonvisual cues to shitsukan perception might well be expected to be less important than might perhaps be suggested on the basis of the unisensory studies that have been reviewed above (though see also Hershberger and Misceo, 1996;Komatsuzaki et al, 2016).…”
Section: Interim Summarymentioning
confidence: 99%
“…Natomiast instrumenty dęte blaszane mogą być częściej oceniane jako nieprzyjemne, jednak dobrze łączą się z odczuwaniem smaku bardzo gorzkiego lub kwaśnego. Zatem muzyka w sklepie, kawiarni czy restauracji może wpływać na smakowitość produktu lub posiłku, podobnie jak dźwięk otwieranej puszki z napojem czy nalewania piwa lub wina do szklanki (Krishna, 2012;Spence i Wang, 2015;Komatsuzaki, Han i Uchida, 2016).…”
Section: Oddziaływanie Dźwiękamiunclassified